The expression and change of giving directives in the language of pre-school children - Ančlauskaitė, Jolita (Lietuvių kalba, 2020)
It is stated that children in their speech master directives at their earliest age and they use them the most frequently. However, it is currently unknown how these directives develop in the Lithuanian language and how their expression changes when a child grows up. This article investigates the change in the number and expression of directives during child’s raising, and what their differences emerge individually by comparing the speech of girls and boys. It is expected that the analysis conducted during the work will contribute to the studies of children’s pragmatic competence in Lithuania, i.e. to establish the most common characteristics typical to the directives used by children, by comparing the directives used by pre-school children at the beginning of the academic year and in its end in order to identify the differences and how children’s speech changes when more intensive formal education starts. The paper involves the gender dimension by expecting that differences in the language may be also envisaged between girls and boys. The object of this paper is directives used in spontaneous dialogues of pre-school children. The work material consists of 12 children’s dialogues, which have been transcribed and encoded morphologically by Software CHILDES (Child Language Data Exchange System). The following methods were applied during the work: 1) Cross-sectional (by sampling the subjects and gathering the work material); 2) Linguistic text corpora (by filing and analysing a child language text by Software CHILDES); 3) Comparative (by comparing: a) Data of the speech of girls and boys; b) Data of the speech of five-year-olds and six-year-olds). After summarising the results of this research, it might be stated that even pre-school children can use different forms of directive types. As it was expected, more difficult constructions and forms develop by experiencing more different situations, what is seen when the stages change (at the beginning and in the end of the study). The gender dimension highlighted in the study suggests that considerable differences were not identified, and most cases reported indicate more common charcteristics.
Keywords: psycholinguistics; children’s language; directives; expression of directives